2022
DOI: 10.1186/s12889-022-14497-8
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory health among adolescents living in the Highveld Air Pollution Priority Area in South Africa

Abstract: Background Air pollution is a global, public health emergency. The effect of living in areas with very poor air quality on adolescents’ physical health is largely unknown. The aim of this study was to investigate the prevalence of adverse respiratory health outcomes among adolescents living in a known air pollution hotspot in South Africa. Methods Ambient air quality data from 2005 to 2019 for the two areas, Secunda and eMbalenhle, in the Highveld … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The findings from the studies conducted in South Africa suggests air pollution and silica dust significantly impacts NCDs [ 25 32 , 35 ]. Eight studies reported a significant association between air pollution and chronic diseases [ 25 32 ], while one [ 36 ] found no association between air pollution (PM 2.5 , PM 10 , NO 2 , SO 2 , O 3 ) and self-reported respiratory symptoms. This null association may be due to the small sample size (n = 233) and the assumption that air pollution estimates around monitoring stations represent city-wide exposures.…”
Section: Discussionmentioning
confidence: 99%
“…The findings from the studies conducted in South Africa suggests air pollution and silica dust significantly impacts NCDs [ 25 32 , 35 ]. Eight studies reported a significant association between air pollution and chronic diseases [ 25 32 ], while one [ 36 ] found no association between air pollution (PM 2.5 , PM 10 , NO 2 , SO 2 , O 3 ) and self-reported respiratory symptoms. This null association may be due to the small sample size (n = 233) and the assumption that air pollution estimates around monitoring stations represent city-wide exposures.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of all this is that poor air quality leads to deterioration of the environment and people's health and well-being. This includes increased premature deaths, heart and lung diseases, and cancer (Millar et al 2022). and also causes or exacerbates underlying conditions such as asthma, emphysema, bronchitis, and tuberculosis (Trustees for the time being of Groundwork Trust v Minister of Environmental Affairs (39724/2019) [2022] ZAGPPHC 208) (South Africa).…”
Section: Air Pollution In the Mpumalanga Highveldmentioning
confidence: 99%